Surgical Aortic Valve Replacement For Bicuspid And Tricuspid Valve Disease: 7-Year Outcomes In >1100 Patients - Labrousse, Louis (2025)
Introduction: Bicuspid aortic valve affects 0.5-2% of the population in developed countries. Given uncertainties about the best aortic valve replacement (AVR) option in this often younger, low-risk, population, it is important to understand how newer bioprostheses perform in these patients. The primary objective of this analysis was to compare 7-year outcomes of surgical AVR (SAVR) with the Avalus bioprosthesis between patients with a congenital bicuspid or tricuspid valve. Methods: This prospective, non-randomized study included 1132 patients with aortic valve stenosis or chronic severe aortic regurgitation who underwent successful SAVR with the Avalus bioprosthesis. Patients were categorized into bicuspid (n=339) and tricuspid (n=775) groups; 18 patients had unknown etiology. Kaplan-Meier analyses estimated valve-related adverse events over 7 years. Multivariable Cox proportional hazard models with propensity score adjustments evaluated the association of valve etiology with clinical outcomes, and a multivariable analysis identified risk factors for all-cause mortality. Results: Patients with a tricuspid valve were older with more advanced heart failure symptoms and a higher mean Society of Thoracic Surgeons risk score (P<0.01). At 7 years postimplant, mortality was lower [8.9% (95% CI: 5.9%-13.4%) versus 21.3% (95% CI: 18.1%-24.9%), P<0.01] and non-structural valve dysfunction was higher in the bicuspid cohort [2.9% (95% CI: 1.5%-5.5%) versus 0.6% (95% CI: 0.2%-1.6%), P<0.01]. Other safety parameters were not significantly different. In the bicuspid and tricuspid cohorts, the respective mean effective orifice area was 2.0±0.5 and 2.0±0.5 at 7 years, and the respective mean aortic gradient was 13.6±6.4 and 14.1±5.7. Reintervention rates were low [6.8% (95% CI: 4.1%-10.9%) versus 5.4% (95% CI: 3.7%-7.8%), P=0.54] in both cohorts. Conclusions: SAVR with the Avalus bioprosthesis yielded excellent 7-year outcomes for patients with either a congenital bicuspid or tricuspid valve. Hemodynamic performance and reintervention rates were similar between cohorts with low rates of other valve-related adverse events.